Skoblo T.S., Romaniuk S.P.,Sidashenko A.I., Omelchenko L.V., Olejnik A.K. Increase of wear-resistance of simple and reduced items by coating by application of modification by secondary raw materials. - Скобло, Т.С.; Романюк, С.П.; Сидашенко, А.И.; Омельченко, Л.В.; Олейник, А.К. (Problems of Tribology, 2017)
Modifying method using the magnetic component of recycled for hardening and restoring the surfaces of worn parts made of low-alloy and carbon steels is considered. The influence of the technology of the coating modifying by the magnetic component of the detonation charge during hardfacing on the structure, hardness and wear resistance of the restored layer is researched. It is established that the wear resistance of the restored part is increased by 25% by the use of the proposed method. . Key words: surfacing, low-alloy steels, detonation charge, magnetic component, wear resistance.